Pemilihan Presiden 2004 dan Kualitas Demokrasi - Cipto, Bambang (Unisia, 2016)
The direct presicent election in 2004 have a-unique aspect according to the change of democratitation, not just because this is the first time people choose directly their own president, but this is alo a transition of democracy in Indonesia which will shows how good the quality of our democracy. In this election candidate should have "the parallel views" with people feeling and people need, and to arculate what people want Here will apparent how important the use of media to measure who deserve for president among the candidates, is he or she well understand the condition of their society such as poverty, health, unemlpoyment, etc? Or they just use the people as a vehicle to get what they want.